Core Outcome Set-STAndardised Protocol Items: the COS-STAP Statement - Kirkham, Jamie J.; Gorst, Sarah; Altman, Douglas G.; Blazeby, Jane M.; Clarke, Mike; Tunis, Sean; Williamson, Paula R. (Current controlled trials in cardiovascular medicine, 2019)
Background Several hundred core outcome set (COS) projects have been systematically identified to date which, if adopted, ensure that researchers measure and report those outcomes that are most likely to be relevant to users of their research. The uptake of a COS by COS users will depend in part on the transparency and robustness of the methods used in the COS development study, which would be increased by the use of a standardised protocol. This article describes the development of the COS-STAP (Core Outcome Set-STAndardised Protocol Items) Statement for the content of a COS development study protocol. Methods The COS-STAP Statement was developed following the Enhancing the Quality and Transparency Of Health Research (EQUATOR) Network’s methodological framework for guideline development. This included an initial item generation stage, a two-round Delphi survey involving more than 150 participants representing three stakeholder groups (COS developers, journal editors and patient and public involvement researchers interested in COS development), followed by a consensus meeting with eight voting participants. Results The COS-STAP Statement consists of a checklist of 13 items considered essential documentation in a protocol, outlining the scope of the COS, stakeholder involvement, COS development plans and consensus processes. Conclusions Journal editors and peer reviewers can use the guidance to assess the completeness of a COS development study protocol submitted for publication. By providing guidance for key content, the COS-STAP Statement will enhance the drafting of high-quality protocols and determine how the COS development study will be carried out.